Growth and Instability in Area, Production and Productivity of Grape Crop in Afghanistan - Younisi, Hamidullah; Farid, Zabihullah; Joya, Khalid (Journal for Research in Applied Sciences and Biotechnology, 2023)
Grapes constitute a widely grown fruit in Afghanistan. Grapes can be grown just in anywhere but mostly in Kabul, Parwan, Kandahar, Zabul and Ghazni provinces. In Afghanistan there are three local varieties that offer the best commercial return for export: Shindokhani, Kishmishi and Taifi. New commercial varieties are also being introduced, such as Thompson Seedless and Red Globe, and are beginning to make inroads into foreign markets. The present study estimates the growth rate and instability of area, production, productivity of grape in top five provinces and Afghanistan as a whole during years 2011-12 to 2019-20. To analyse the growth rate and instability of area, production and productivity of grape, the statistical tools like Compound growth rate (CGR) and Coefficient of Variation (CV) were used. The result of the study showed that, the CGR for production in the Kandahar and Ghazni provinces were found positive and significant. While negative growth rate were found in Kabul, Parwan and Zabul provinces. The instability of production and area were very high in Kandahar province compare to the other selected provinces.